IMPLEMENTASI TRI DARMA PERGURUAN TINGGI OLEH DOSEN PAK TAHUN AJARAN 2018/2019 DI STT â€œKRISTUS ALFA OMEGAâ€ SEMARANG - Yulia, Tantri (Shift Key : Jurnal Teologi dan Pelayanan, 2018)
The main tasks of the lecturer are summarized into three main tasks, namely in the fields of teaching, research and community service. The teaching field is related to the ability of lecturers to deliver teaching material, the research assignment related to the development of knowledge and the field of community service is lecturer service which is a contribution of lecturers in community life by sharing their experiences and knowledge in accordance with the specifications of the fields used for welfare to the community. The limitation of the problem in this study is that there are still lecturers of the Christian Religious Education study program at STT Kristus Alfa Omega Semarang who have not implemented the Tri Darma of Higher Education.The formulation of the problem in this study is how big is the level of implementation of the Tri Darma of Higher Education by PAK lecturers in the academic year 2018/2019 at STT "Kristus Alfa Omega" Semarang? The purpose of the study was to determine the level of implementation of the Tri Darma of Higher Education in the field of teaching by PAK lecturers in the academic year 2018/2019 at STT "Kristus Alfa Omega" Semarang. Research hypothesis: Allegedly Implementation of Higher Education Tri Darma by PAK Lecturers in Academic Year 2018/2019 in STT "Kristus Alfa Omega" Semarang in the medium category or equal to 60% of the maximum value not accepted because the results of the calculation above obtained a hypothesis value of 83% of maximum value.